Combining good dispersion with tailored charge trapping in nanodielectrics by hybrid functionalization of silica - He Xiaozhen (De Gruyter, 2021)
Fumed silica-filled polypropylene (PP)-based nanodielectrics were studied in this work. To not only improve the dispersion of the silica but also introduce deep charge traps into the polymeric matrix, five types of modified silicas were manufactured with different surface modifications. The modified silica surfaces comprise an inner and a surface layer. The inner layer contains a polar urethane group for tailoring the charge trap properties of the PP/propylene–ethylene copolymer nanocomposites, whereas the surface layer consists of hydrocarbons (ethyl-, tert-butyl-, cyclopentyl-, phenyl-, or naphthalenyl moieties) in order to gain a good dispersion of the silica in the unpolar polymer blend. Scanning electron microscopic pictures proved that these tailored silicas show a much better dispersion than the unmodified one. Thermally stimulated depolarization current measurements revealed the ability of the silica to introduce deep charge traps with low trap density. The trap depth distribution depends on the type of the unpolar surface layer consisting of the different hydrocarbons. Among these five differently modified silicas, the introduction of the one with a surface layer consisting of tert-butyl moieties resulted in the lowest charge injection and the lowest charge current in the nanocomposite, proving good dielectric performance. Additionally, this silica exhibits good dispersion in the polymeric matrix, indicating a promising performance for nanodielectric application.